Precision Flux Control of Linear Reluctance Actuator Using the Integral Sliding Mode Method - Miao, Qian; Liu, Yang; Tan, Jiu Bin (Frontiers in Energy Research, 2022)
The performance of the actuator is becoming increasingly important in the ultra-precision stage. However, the traditional Lorentz motors with given mechanical parameters cannot provide enough force for the next-generation motion stage in the semiconductor industry since they achieve a physical limit of power factor. To tackle this problem, this study develops a novel-driven approach and its control strategy for high-dynamic stages. Explicitly, the proposed method utilizes a linear reluctance motor as an actuator, which could promote the continuous thrust significantly. A heuristic optimization-based Bouc–Wen model is established to describe the nonlinear behavior of the novel actuator. Also, a flux control algorithm based on the integral sliding mode is derived and adjusted for precision thrust generation. Comparative simulations on a specific linear reluctance motor confirm the effectiveness and superiority of the proposed method and show that it has the ability to conquer the force nonlinearity of the novel actuator.